Concurrent Treatment of 1, 4‐Dioxane and Chlorinated Aliphatics in a Groundwater Recirculation System Via Aerobic Cometabolism. Issue 3 (22nd June 2018) - Chu, Min‐Ying Jacob; Bennett, Peter J.; Dolan, Mark E.; Hyman, Michael R.; Peacock, Aaron D.; Bodour, Adria; Anderson, Richard Hunter; Mackay, Douglas M.; Goltz, Mark N.
Abstract: This research demonstrates that groundwater contaminated by a relatively dilute but persistent concentration of 1, 4‐dioxane (1, 4‐D), approximately 60 μg/L, and chlorinated aliphatic co‐contaminants (1.4 to 10 μg/L) can be efficiently and reliably treated by in situ aerobic cometabolic biodegradation (ACB). A field trial lasting 265 days was conducted at Operable Unit D at the former McClellan Air Force Base and involved establishing an in situ ACB reactor through amending recirculated groundwater with propane and oxygen. The stimulated indigenous microbial population was able to consistently degrade 1, 4‐D to below 3 μg/L while the co‐contaminants trichloroethene (TCE) and 1, 2‐dichloroethane (1, 2‐DCA) were decreased to below 1 μg/L and 0.18 μg/L, respectively. A stable treatment efficiency of more than 95% removal for 1, 4‐D and 1, 2‐DCA and of more than 90% removal for TCE was achieved. High treatment efficiencies for 1, 4‐D and all co‐contaminants were sustained even without propane and oxygen addition for a 2‐week period.